Pocket poems - Katz, Bobbi; Hafner, Marylin (Dutton Children's Books, 2004)
A collection of short poems by such authors as: Gwendolyn Brooks, Emily Dickinson, Emily George, Nikki Giovanni, Eve Merriam, and Charlotte Pomerantz.